An Exploratory Quarterly Econometric Model of Effective Demand in the Postwar U. S. Economy - Liu, Ta-Chung (Econometrica, 1963)
of the postwar U. S. economy in the Tinbergen-Klein [32, 15, and 16] tradition,2 and to apply the model to an analysis of certain types of monetary and fiscal policy. The model is crude and exploratory,3 and the analysis is in aggregate terms. Needless to say, the U. S. economy cannot be adequately described by such a simple model, and the findings are necessarily highly tentative. The model and the simulations presented here are the initial result of a limited attempt to gain some knowledge about certain aspects of the economy in quantitative terms and to throw some light on the problems involved. The lag in effect in monetary and fiscal policy (Baumol [3], Culbertson [7 and 8], and Friedman [12]) is a case in point. Such a problem cannot be settled by theoretical analysis. An indication of the answer to the question can only be obtained through a quantitative study, however crude the approach and the indication may be. The model is constructed on fifty quarterly observations from the third quarter of 1947 to the fourth quarter of 1959. The structural equations are presented in Appendix A, with the variables and the sources of data listed in Appendix B. Sections 1-3 describe the model. The investment and consumption functions are presented in Section 1. A sub-model on inventory and price movements is formulated in Section 2. Functions for monetary and certain other variables are presented in Section 3. Extrapolations for the magnitudes of the major components of gnp are computed for 1960 and the first quarter of 1961 from the respective individual equations in Sections 1 1 The author wishes to express appreciation to the Ford Foundation whose faculty research fellowship made this research possible, to the Social Science Research Center of Cornell University for grants to support the initial computations, and to his colleagues at the Cornell Computing Center for their untiring cooperation. He is indebted to Marc Nerlove and A. S. Goldberger for discussion at various stages of the preparation